2019
DOI: 10.1021/acs.inorgchem.9b01237
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of the Electronic Structure and Magnetic Properties of Oxo-Bridged Uranyl(V) Dinuclear and Trinuclear Complexes

Abstract: Theoretical investigation of the electronic structure and magnetic properties of oxo-bridged uranyl(V) dinuclear and trinuclear complexes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 138 publications
2
18
1
Order By: Relevance
“…More interestingly, another dinuclear U(V)−U(V) complex reported by Walensky and co-workers, 70 where the two paramagnetic U(V) centres linked by the para-benzoquinone exhibit a weak AF coupling (J = −0.6 cm -1 ). These findings are also valid for oxo-bridged complexes, 34,35 for which some of us revealed that the magnetic exchange coupling is more sensitive to changes in the U−U distance and UOU angles at core geometry than to modifications in the coordination environment around the magnetic core. Conversely, for the [{U(N t Bu) 2 (I) 2 (bpy)} 2 ] model system, Spencer et al 30 calculated at the DFT/BS level a coupling constant J of −12 cm -1 , smaller than in other para-bis(imido) diuranium(V) systems with larger U(V)−U(V) distances.…”
Section: A C C E P T E Dsupporting
confidence: 61%
See 1 more Smart Citation
“…More interestingly, another dinuclear U(V)−U(V) complex reported by Walensky and co-workers, 70 where the two paramagnetic U(V) centres linked by the para-benzoquinone exhibit a weak AF coupling (J = −0.6 cm -1 ). These findings are also valid for oxo-bridged complexes, 34,35 for which some of us revealed that the magnetic exchange coupling is more sensitive to changes in the U−U distance and UOU angles at core geometry than to modifications in the coordination environment around the magnetic core. Conversely, for the [{U(N t Bu) 2 (I) 2 (bpy)} 2 ] model system, Spencer et al 30 calculated at the DFT/BS level a coupling constant J of −12 cm -1 , smaller than in other para-bis(imido) diuranium(V) systems with larger U(V)−U(V) distances.…”
Section: A C C E P T E Dsupporting
confidence: 61%
“…The reliability of the BS approach using Yamaguchi's formula has been discussed earlier and validated, 19,[30][31][32][33][34][35]56,57 where it was shown that computations of the magnetic coupling constants at the B3LYP level generally lead to satisfactory results and good agreement with both high-level post-HF computations and experimental findings. complexes.…”
Section: A Geometry Optimizationsmentioning
confidence: 84%
“…The U(V) and U(VI) oxidation states tend to form short covalent axial trans dioxo bonds oen referred to as uranyl (UO 2 1+ ¼ U(V)-yl and UO 2 2+ ¼ U(VI)-yl). The electronic structure of the U(VI)-yl moiety has been the subject of intensive study, [15][16][17] but less reports are available on U(V)-yl [18][19][20][21] because uranyl(V) species are much less stable in aerobic aqueous conditions than uranyl(VI) species and their synthetic preparation is not trivial. [22][23][24] Only one natural uranium mineral, wyartite (CaU(V)(UO 2 ) 2 (CO 3 )O 4 (OH)$7H 2 O) was so far reported to contain U(V).…”
mentioning
confidence: 99%
“…Density functional theory (DFT) calculations have been used for the optimization of the crosslinked polymer at BP86 [24,25] level and TZP [26][27][28][29][30] basis set using the Amsterdam Density Functional (ADF2019.105) [31] software. Frequency analysis was done for the confirmation of the optimized structures as there was no imaginary frequencies that correspond to their lowest energy conformation.…”
Section: Methodsmentioning
confidence: 99%